2016
DOI: 10.7853/kjvs.2016.39.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ticks carrying Severe Fever with Thrombocytopenia Syndrome Virus (SFTSV) around Jiri walking trails of Jeollanam-do, Korea

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging disease characterized by fever and thrombocytopenia. Haemaphysalis longicornis ticks comprise the major population of ticks in the environment and have been considered as the main vector for SFTS virus (SFTSV). Here we investigated the distribution of ticks carrying SFTSV collected from the environment using the dragging or sweeping methods during April∼October 2015 in Jeollanam-do, Korea. Sampling was taken from Songjeong, Omi, Bangkwang, Sando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…For H. flava, 146 (4.7%) were collected with tick traps and 73 (4.7%) were collected with the flagging method. In other studies, 161 (85%) H. longicornis were collected in Chungju in 2002 and 2003 [11], 158 (95.7%) were collected in Gangwon-do in 2015 [3], and 3,823 (98.8%) were collected in Jeonnam in 2016 [12], showing similar percentage patterns to this survey. It has been confirmed that H. longicornis is distributed widely not only in inland areas, but also in www.kjcls.org all parts of Korea, including Jeju Island.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…For H. flava, 146 (4.7%) were collected with tick traps and 73 (4.7%) were collected with the flagging method. In other studies, 161 (85%) H. longicornis were collected in Chungju in 2002 and 2003 [11], 158 (95.7%) were collected in Gangwon-do in 2015 [3], and 3,823 (98.8%) were collected in Jeonnam in 2016 [12], showing similar percentage patterns to this survey. It has been confirmed that H. longicornis is distributed widely not only in inland areas, but also in www.kjcls.org all parts of Korea, including Jeju Island.…”
Section: Discussionsupporting
confidence: 84%
“…As a way to diagnose SFTSV, Yun et al [14] examined the medium segment gene, a specific gene of SFTSV, using RT PCR for H. longicornis in 189 pools, and found 18 positive pools. In a study conducted in Jeollanam-do Province in 2016, SFTSV was not detected in gene analysis using the 2X OneStep RT-PCR method with 127 pooled ticks [12]. In the present study, 3,090 ticks (235 pools) collected using tick traps and 1,569 (129 pools) collected using the flagging method were monitored for SFTSV by RT-PCR.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations